RESEARCH OF THE APPLICATION OF COMPOSITE MATERIAL IN THE METAL CONSTRUCTION OF EXCAVATOR WORKING EQUIPMENT - Спільник, Михайло; Кроль, Роман; Ужеловський, Андрій; Ужеловський, Валентин (SWorldJournal, 2024)
The development of mechanical engineering is accompanied by a rejection from typical prefab structures with a large metal capacity, which is connected with the general trend of decreasing costs for structural materials and the global economic situation.